SIMULAÇÕES COM MODELO FÍSICO PARA CAPTURA DE PREFERÊNCIAS DO USUÁRIO NO PROJETO HABITACIONAL - Souza, Marcio Presente de; Imai, César; Azuma, Maurício Hidemi (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This paper addresses the problem of communication difficulties between designers and lay users during the initial stages of the housing design process. The objective of the study is to demonstrate the application of a three-dimensional physical model associated with two immersive elements, a human scale figure and a camera + notebook, as a tool to capture user preferences. The method used consists of two different simulation dynamics, and the application of cognitive walkthrough, verbal protocol and participant observation. The results showed that each simulation model captures different types of information about the user and stimulates, in a different way, their perception about the architectural design.